(untitled) (TAJ: Journal of Teachers Association, 2018)
Background: Bronchial asthma isone of the major health problems and causes of chronic morbidity and mortality in Bangladesh as well as worldwide. ECG was performed to observe changes among the patients of bronchial asthma. Objectives: To observe ECG changes among the patients ofbronchial Asthma. Methods: It was a cross-sectional observational study carried out in the Department of Medicine, Rajshahi Medical College Hospital, Rajshahi from July, 2010 to June, 2012. According to inclusion and exclusion criteria 73 people having bronchial asthma were selected. Thorough history, physical examination and spirometric along with ECG assessment were done. Results: In case of bronchial asthma, 03(4.11%) cases showed ECG changes and 70 (95.89%) cases showed normal ECG. Conclusion: In this study, ECG changes were 4.11% in bronchial asthma patients. TAJ 2016; 29(2): 57-61